SIMPLE AND COMPLEX PROBLEMS IN PRIMARY SCHOOL STUDENTS - U.Akhmedova; F.Mukhammadqodirova (Western European Studies, 2025)
This article discusses the essence of the system of mathematical concepts taught to students in primary school mathematics lessons, as well as the role and importance of complex problems in developing students' mathematical understanding and thinking. The article shows effective ways of forming logical thinking by selecting problems corresponding to the age and psychological characteristics of primary school students, teaching them to solve them step by step.
Keywords: mathematics; mathematical knowledge; mathematical concept and thinking